Cognitive Frailty as a Predictor of Mortality in Older Adults: A Longitudinal Study in Peru - Vargas-Torres-Young, Diego A.; Salazar-Talla, Leslie; Cuba-Ruiz, Sofia; Urrunaga-Pastor, Diego; Runzer-Colmenares, Fernando M.; Parodi, Jose F. (Frontiers in Medicine, 2022)
Objective: To evaluate the role of cognitive frailty and its components as risk factors of mortality in older adults of the Centro Médico Naval (CEMENA) in Callao, Peru during 2010-2015. Methods: We performed a secondary analysis of data from a prospective cohort that included older adults (60 years and older) treated at the CEMENA Geriatrics service between 2010-2015. Frailty was defined as the presence of three or more criteria of the modified Fried Phenotype. Cognitive impairment was assessed using the Peruvian version of the Mini Mental State Examination (MMSE), considering a score less than 21 as cognitive impairment. Cognitive frailty was defined as the coexistence of both. In addition, we included sociodemographic characteristics, medical and personal history, as well as the functional evaluation of each participant. Results: We included 1,390 older adults (mean follow-up: 790.4 days), with a mean age of 78.2 ± 8.5 years and 59.6% (n=828) were male. Cognitive frailty was identified in 11.3% (n=157) and 9.9% (n=138) died during follow-up. We found that cognitive frailty in older adults (aHR=3.57; 95%CI: 2.33-5.49), as well as its components, such as sedentary behavior and cognitive impairment (aHR=7.05; 95%CI: 4.46-11.13), weakness and cognitive impairment (aHR=6.99; 95%CI: 4.41-11.06), and exhaustion and cognitive impairment (aHR=4.51; 95%CI: 3.11-6.54) were associated with a higher risk of mortality. Conclusion: Cognitive frailty and its components were associated with a higher risk of mortality in older adults. It is necessary to develop longitudinal studies with a longer follow-up and that allow evaluating the effect of interventions in this vulnerable group of patients to limit adverse health outcomes, including increased mortality.